Vibrotactile motors on stationary arm as directional feedback to correct arm posture - Causo, Albert (2013)
When appropriate sensing and feedback are utilized, automation could be used in occupational therapy to aid patient rehabilitation. Previous studies have shown the feasibility of a system that uses inertial measurement units (IMUs) for sensing and vibrotactile feedback for correction. In this paper, we present a similar system with a reconfigured vibrotactile feedback. Multiple vibrotactile motors are positioned on the stationary arm of the subject to provide consistent directional feedback on the moving arm. Up to six vibrotactile motors are employed to provide direction guidance in 3 dimensional cartesian space. Experiments with seven volunteers in correcting five reference postures show the robustness of this system for an accurate and fast arm posture correction.